The Influence of E-Service Quality and E-Trust on E-Satisfaction and E-Loyalty among Shopee Users - Wong, Kelvin; Widjaja, Fitri Novika; Megawati, Veny Megawati (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2026)
This study investigates the relationships between electronic service quality, electronic trust, electronic satisfaction, and electronic loyalty among Shopee users in Surabaya, Indonesia, addressing ongoing inconsistencies in e-commerce loyalty research. While prior studies often assume electronic satisfaction as a key mediator, this research offers novel empirical evidence challenging that assumption in the context of highly competitive electronic marketplaces. Using a quantitative causal design, data were collected from 248 Shopee users who had made purchases within the past six months and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.1.1.5. The findings demonstrate that website security, convenience, and electronic trust significantly enhance electronic satisfaction, whereas reliability and responsiveness do not. In contrast, electronic loyalty is directly influenced by website security, reliability, and electronic trust, while electronic satisfaction shows no mediating effect. These results contribute theoretically by repositioning electronic trust and security as more central drivers of loyalty than satisfaction in mature e-commerce platforms, thereby extending existing electronic service quality and loyalty models. From a managerial perspective, the study highlights the strategic importance of strengthening transaction security, system reliability, and trust-building mechanisms to sustain user loyalty in increasingly saturated digital commerce environments.